Differentiation-associated urothelial cytochrome P450 oxidoreductase predicates the xenobiotic-metabolizing activity of "luminal" muscle-invasive bladder cancers - Baker, Simon C; Arlt, Volker M; Indra, Radek; Joel, Madeleine; Stiborová, Marie; Eardley, Ian; Ahmad, Niaz; Otto, Wolfgang; Burger, Maximilian; Rubenwolf, Peter; Phillips, David H; Southgate, Jennifer (Molecular carcinogenesis, 2018)
Extra-hepatic metabolism of xenobiotics by epithelial tissues has evolved as a self-defence mechanism but has potential to contribute to the local activation of carcinogens. Bladder epithelium (urothelium) is bathed in excreted urinary toxicants and pro-carcinogens. This study reveals how differentiation affects cytochrome P450 (CYP) activity and the role of NADPH:P450 oxidoreductase (POR). CYP1A1 and CYP1B1 transcripts were inducible in normal human urothelial (NHU) cells maintained in both undifferentiated and functional barrier-forming differentiated states in vitro. However, ethoxyresorufin O-deethylation (EROD) activity, the generation of reactive BaP metabolites and BaP-DNA adducts, were predominantly detected in differentiated NHU cell cultures. This gain-of-function was attributable to the expression of POR, an essential electron donor for all CYPs, which was significantly upregulated as part of urothelial differentiation. Immunohistology of muscle-invasive bladder cancer (MIBC) revealed significant overall suppression of POR expression. Stratification of MIBC biopsies into "luminal" and "basal" groups, based on GATA3 and cytokeratin 5/6 labeling, showed POR over-expression by a subgroup of the differentiated luminal tumors. In bladder cancer cell lines, CYP1-activity was undetectable/low in basal PORlo T24 and SCaBER cells and higher in the luminal POR over-expressing RT4 and RT112 cells than in differentiated NHU cells, indicating that CYP-function is related to differentiation status in bladder cancers. This study establishes POR as a predictive biomarker of metabolic potential. This has implications in bladder carcinogenesis for the hepatic versus local activation of carcinogens and as a functional predictor of the potential for MIBC to respond to prodrug therapies.
Keywords: down regulace; Gene Expression Regulation, Neoplastic; Male; Cytochrome P-450 CYP1B1; Tissue Array Analysis; Cell Line, Tumor; xenobiotika; Cytochrome P-450 CYP1A1; nádory močového měchýře; regulace genové exprese u nádorů; urotel; buněčná diferenciace; Aged; cytochrom P-450 CYP1A1; senioři; mužské pohlaví; čipová analýza tkání; urothelium; Urothelium; cytochrom P450 CYP1B1; aryl hydrocarbon receptor; senioři nad 80 let; systém (enzymů) cytochromů P-450; POR; Down-Regulation; lidé; ženské pohlaví; Cytochrome P-450 Enzyme System; CYP1A1; Humans; Xenobiotics; Aged, 80 and over; CPR; Urinary Bladder Neoplasms; nádorové buněčné linie; Female; lidé středního věku; Cell Differentiation; Middle Aged